Toward stabilization of formamidinium lead iodide perovskites by defect control and composition engineering - Yuhang Liang; Feng Li; Xiangyuan Cui; Taoyuze Lv; Catherine Stampfl; Simon P. Ringer; Xudong Yang; Jun Huang; Rongkun Zheng (Nature Communications, 2024)
Abstract Phase instability poses a serious challenge to the commercialization of formamidinium lead iodide (FAPbI3)-based solar cells and optoelectronic devices. Here, we combine density functional theory and machine learning molecular dynamics simulations, to investigate the mechanism driving the undesired α-δ phase transition of FAPbI3. Prevalent iodine vacancies and interstitials can significantly expedite the structural transition kinetics by inducing robust covalency during transition states. Extrinsically, the detrimental roles of atmospheric moisture and oxygen in degrading the FAPbI3 perovskite phase are also rationalized. Significantly, we discover the compositional design principles by categorizing that A-site engineering primarily governs thermodynamics, whereas B-site doping can effectively manipulate the kinetics of the phase transition in FAPbI3, highlighting lanthanide ions as promising B-site substitutes. A-B mixed doping emerges as an efficient strategy to synergistically stabilize α-FAPbI3, as experimentally demonstrated by substantially higher initial optoelectronic characteristics and significantly enhanced phase stability in Cs-Eu doped FAPbI3 as compared to its Cs-doped counterpart. This study provides scientific guidance for the design and optimization of long-term stable FAPbI3-based solar cells and other optoelectronic devices through defect control and synergetic composition engineering.